INVESTIGATION OF HOLLOW SLUGS OF SILUMIN AK18 BY MEANS OF FROSTING ON WATER-COOLED ROD - E. I. Marukovich; V. Ju. Stetsenko; K. N. Baranov (Литьë и металлургия)
The possibility of production of hollow billets with diameter 35 mm of silumin AK18 by means of silvering on water-cooled bar is shown.